Acute suppurative thyroiditis Presentation of a clinical case and literature review - Oddone, Nicolás; Rodríguez, Gustavo; Balboa, Oscar (Cirugía del Uruguay, 2004)
Acute suppurated thyroiditis constitutes a clinica/ situation which is relatively rare due to the fact that the intrinsic characteristics of this body result in great resistance against bacteria/ co/onization. As from the advent of antibiotics, on/y sporadic cases of infections in the thyroid gland have been published. In our media we have not been ab/e to find a single publication on this tapie. The patient is a 33 year o/d woman, suffering from acute suppurated thyroiditis within the context of multinodular goitre, originating in an entero invasive diarrhea due to Sa/monella typhimurium. The interest of this paper /ies in the fact that it is difficult to establish diagnosis and on the exceptional nature of this pathology.